Effects of attentional focus and dual-tasking on conventional deadlift performance in experienced lifters - Chan, A.; Robertson, G. E.; Lajoie, Y. (International Journal of Kinesiology & Sports Science, 2019)
Background: Previous attentional focus literature suggests that adopting an external focus (EF) results in greater force production through a variety of mechanisms. Objective: The purpose of the present study was to examine the effects of attentional focus and dual-tasking when performing heavily loaded barbell movements that are specific to strength-based sports. Method: Fifteen resistance-trained males (age = 23.3 ± 3.4 years) reported to the laboratory for three visits. The first visit consisted of a five-repetition maximum (5RM) test on the conventional deadlift. During the subsequent sessions, the participants performed a total of twelve single conventional deadlift repetitions while adopting an internal focus (IF), an external focus (EF), or while performing the cognitive task (COG). The IF and EF consisted of focusing on activating the quadriceps and maintaining a straight bar path, respectively. The COG consisted of counting the total occurrence of two single-digits in a sequence of three-digit numbers, separately. Three-dimensional motion capture and force platforms were used to collect kinematic and kinetic data. Results: No significant differences were found between the IF, the EF and the COG for lift duration, peak barbell velocity, peak vertical ground reaction force, area of 95% confidence ellipse, peak hip moments and peak hip powers. Adopting an EF significantly reduced variability of the barbell trajectory and centre of pressure (COP) in the anterior-posterior direction. Mean velocity of COP was also significantly lower for the EF. Conclusion: Our findings suggest that adopting an EF may lead to greater postural stability when performing heavily loaded barbell movements.